Mathematical Model for Filling in the Dome-Separator Plant for the Elimination of the Near Bottom Hydrocarbon Flow - Askatovich Nasyrov, Azat; Aleksandrovich Chiglintsev, Igor; Anatolievich Lepikhin, Sergey; ., . (International Journal of Engineering and Technology, 2018)
The work presents a mathematical model for the hydrocarbon crude extraction from the bottomhole zone by a cylindrical dome-separator. The proposed model allows determining the thermobaric conditions and dynamics of the boundaries of stratified phases in the installation during its operation and analyzing the complications associated with the possibility of formation of gas hydrates.Â Â